SQL Injection Detection using Machine Learning: A Review - Mohammed A M Oudah; Mohd Fadzli Marhusin (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (50-57)